(untitled) (International Journal of Biology and Chemistry, 2018)
Flocculants are widely investigated chemicals, which can be utilized to remedy or purify waste water from industries including petroleum, fabric, mining. Although many types of flocculants have been explored, each flocculant has it’s merits and demerits. Thus, we investigated poly (N,N-diallyl-N,Ndimethylammonium chloride) cationic flocculants. This work reports a novel flocculant which was developed based on the widely used flocculant, poly (N,N-diallyl-N,N-dimethylammonium chloride) (DADMAC) cationic polymers. This newly developed flocculant has not only enhanced flocculant performance, but also provided reusability of this polymer with insertion of crosslinking groups. The new developed copolymer, Poly (DADMAC-co- VEMEA), was synthesized via random radical polymerization approach and characterized by NMR and FTIR. The flocculation performance for these polymers were evaluated and studied by turbidity experiments and zeta-potential measurements. Their flocculation performance over poly (DADMAC) homopolymer can be improved by adding a VEMEA unit to the polymer chain and partially crosslinking the copolymer. This newly developed flocculant can provide new direction in developing flocculants potentially.